2023
DOI: 10.1038/s41598-023-36748-3
|View full text |Cite
|
Sign up to set email alerts
|

Host defense peptides combined with MTA extract increase the repair in dental pulp cells: in vitro and ex vivo study

Abstract: Host Defense Peptides (HDPs) have, in previous studies, been demonstrating antimicrobial, anti-inflammatory, and immunomodulatory capacity, important factors in the repair process. Knowing these characteristics, this article aims to evaluate the potential of HDPs IDR1018 and DJK-6 associated with MTA extract in the repair process of human pulp cells. Antibacterial activity of HDPs, MTA and HDPs combined with MTA in Streptococcus mutans planktonic bacteria and antibiofilm activity was evaluated. Cell toxicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…IDR‐1018 has been reported in the literature as an agent with a wide range of biological activities. In addition to the substantial antibiofilm activity mentioned previously, they also have pro‐ and anti‐inflammatory functions, low cytotoxicity and hemolytic activity (Silva et al., 2023). A study by Silva et al.…”
Section: Amps In Endodontic Treatmentsmentioning
confidence: 93%
See 3 more Smart Citations
“…IDR‐1018 has been reported in the literature as an agent with a wide range of biological activities. In addition to the substantial antibiofilm activity mentioned previously, they also have pro‐ and anti‐inflammatory functions, low cytotoxicity and hemolytic activity (Silva et al., 2023). A study by Silva et al.…”
Section: Amps In Endodontic Treatmentsmentioning
confidence: 93%
“…IDR-1018 has been reported in the literature as an agent with a wide range of biological activities. In addition to the substantial antibiofilm activity mentioned previously, they also have pro-and anti-inflammatory functions, low cytotoxicity and hemolytic activity (Silva et al, 2023). A study by Silva et al (2023) aimed to evaluate the potential of IDR-1018, DJK-6 and their association with MTA extract, in the repair process of the pulp-dentine complex.…”
Section: Amps Mediated Innate Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Host defense peptides (HDPs) are a class of biomolecules that can have both antimicrobial acivity against bacteria, viruses and fungi, as well as performing important immunomodulatory functions in angiogenesis, wound healing, and chemotaxis [12]. In addition, it has been shown that some peptides increase antibiotic action to prevent bio lm formation and eradicate mature bio lms [13]. One example is the synergistic combination of peptide IDR 1018 with low levels of the antibiotics ceftazidime, cipro oxacin, imipenem, or tobramycin, which was able to reduce the concentration of antibiotic required to eradicate bio lms [12,13].…”
Section: Introductionmentioning
confidence: 99%